A fantasy theme analysis of Peter Senge's learning organization - Jackson, Bradley G. (2000)
When it was first articulated in the Fifth Discipline, Peter Senge's vision of the learning organization was one of a number of competing conceptions. This article examines what it was about Senge's vision that enabled it to catch on and be assimilated so rapidly and pervasively into everyday business discourse. The method used in this study is fantasy theme analysis, a dramatistically based method of rhetorical criticism developed by Ernest Bormann that is rooted in symbolic convergence theory. The analysis reveals four interrelated fantasy themes that form the dramatic building blocks of the rhetorical vision of the learning organization. The article examines the organizational and rhetorical strategies that Senge has deployed to sustain widespread interest in his vision. - Reproduced
Keywords: Educational administrative structure; Organizations